2003
DOI: 10.1046/j.1442-9071.2003.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative 5‐fluorouracil versus intraoperative mitomycin C in high‐risk glaucoma filtering surgery: extended follow up

Abstract: These results suggest that both postoperative 5-FU injections and intraoperative MMC application have long-term success in high-risk patients. However, MMC results in a greater decrease in intraocular pressure than 5-FU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 37 publications
2
34
0
1
Order By: Relevance
“…28 Few reports that compared the trabeculectomy with MMC versus 5-FU in uveitic glaucoma have found that both procedures have long-term success in patients at high risk, although, MMC seems to be lowering the IOP more than the 5-fluorouracil. 29,30 Glaucoma drainage devices are recommended in uveitic glaucoma among patients at high risk of trabeculectomy failure, such as aphakic patients, juvenile idiopathic arthritis, previous trabeculectomy failures, or retinal detachment surgery. 31 Da Mata et al 32 reported a success rate of 92% at 1 year with the Ahmed glaucoma drainage device.…”
Section: Discussionmentioning
confidence: 99%
“…28 Few reports that compared the trabeculectomy with MMC versus 5-FU in uveitic glaucoma have found that both procedures have long-term success in patients at high risk, although, MMC seems to be lowering the IOP more than the 5-fluorouracil. 29,30 Glaucoma drainage devices are recommended in uveitic glaucoma among patients at high risk of trabeculectomy failure, such as aphakic patients, juvenile idiopathic arthritis, previous trabeculectomy failures, or retinal detachment surgery. 31 Da Mata et al 32 reported a success rate of 92% at 1 year with the Ahmed glaucoma drainage device.…”
Section: Discussionmentioning
confidence: 99%
“…The success rate of trabeculectomy with postoperative 5-fluorouracil injections was 70% after median follow-up of 35 months [24]. There have been few reports of studies of MMC trabeculectomy in uveitic glaucoma and reports to date have shown no clear advantage over 5-fluorouracil in terms of IOP control [25][26][27], although in high-risk glaucoma surgery in general, MMC lowers the IOP more than 5-fluorouracil, and may do so for a longer duration [28,29]. Glaucoma drainage devices are worth considering in uveitic glaucoma with high risk of trabeculectomy failure such as aphakic patients, juvenile idiopathic arthritis, previous trabeculectomy failures, or retinal detachment surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Bleb fibrosis and encapsulation were treated with 5-fluorouracil (5-FU) subconjunctival injections (0.2 ml, 5 mg). Injections were made daily for 5 consecutive days or until the moment when fibrosis regression and IOP normalisation were observed or there occurred complications associated with antimetabolite administration 17 . In these cases suturolysis was performed with an argon laser (50 mm, 100 ms, 800-1000 mW).…”
Section: Methodsmentioning
confidence: 99%